A poesia de Mario Quintana e a formação de leitores literários críticos na educação de jovens e adultos (EJA) - Santos, Vânia de Oliveira Resende (2023)
This is a research developed in the Professional Master's Stricto Sensu of the Postgraduate Program in Teaching in Basic Education of the Center for Teaching and Applied Research to Education (CEPAE) of the Federal University of Goiás (UFG), between the years 2021 to 2023. Faced with many debates around the difficulties that Basic Education students have in relation to reading and interpreting texts, the proposal for this work arose, which was to investigate how the reading of Mario Quintana's poetry can contribute to the formation of critical literary readers in the Youth and Adult Education (EJA) and so that, from familiarization with poetry, the student reader is able to understand his subjective and collective condition and perceive himself in his integral formation. It also seeks to minimize (or demystify) students' resistance to reading, in addition to contributing to the formation of critical literary readers and making them aware of their condition as active men in the reality in which they live and as actors of the social role that develop in society. The central question of this research aims to find answers to: "How can the reading of Mario Quintana's poetry contribute to the formation of critical readers who are aware of their subjective and collective condition?" To support this research, the theoretical basis will be discussed with the texts of Candido (2004), Paz (1982), Freire (1987), Andruetto (2017), Pilatti (2018), Moisés (2019), Pinheiro (2002), Yokozawa (2006), among others. This project is justified by the teacher's need to mediate and guide the construction of knowledge through the reading of poetic literary texts that reflect everyday life and relate to the experiences of EJA students. The methodological path will be developed through action-research, having as a corpus of analysis the works Apontamentos de História Supernatural, Caderno H and Espelho Mágico, by Mario Quintana. To this end, there will be involvement of the teacherresearcher, students and other employees interested in the topic. In the course of execution, a socioeconomic questionnaire will be applied for the knowledge of the students and, in the sequence, several reading activities of the poet's texts. The educational product is an e-book: Between verses and affections: Reading poetry in EJA, which will be available in the appendices and in the UFG repository. This product is instructional and expository, containing the results obtained after the application of the pedagogical action/intervention carried out based on a Didactic Sequence (SD). The e-book will describe the activities carried out and the productions of the EJA students. In this way, the results were expressive and satisfactory